Interpersonal Coordination between Female Soccer Players: Leader-Follower Roles within a Collision-Avoidance Task - Courtney A Fernandes; Grant E Norte; Sarah M Schwab; Alli Gokeler; Amanda Murray; David M Bazett-Jones; David A Sherman (International Journal of Sports Physical Therapy)
# Background/Purpose